Situation and Prevention of Childhood Obesity and Overweight - Rattananupong, Thanapoom (Journal of Health Science of Thailand, 2017)
Overweight and obesity are defined as abnormal or excessive fat accumulation that represents risk to health problems. Overweight and obesity are major risk factors for numbers of chronic diseases, including diabetes mellitus, cardiovascular diseases, cancer and sleep problems. The World Health Organization (WHO) reports an increasing prevalence of overweight and obesity in all age groups. Nowadays, more overweight persons or obesity persons are found not only among adult population but also among children and adolescents. This article describes summary of reviewed literatures on childhood obesity, overweight and recommends research questions for future study.